Sistem Administrasi Pelayanan Rukun Tetangga Dengan Framework PIECES Untuk Kepuasan Pengguna Berbasis Android - Rima Tamara Aldisa; Puspa Ayu Soleha (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
This research aims to build a pillar-saving administration system aimed at helping residents around the Jagakarsa area, South Jakarta. With this system, it can make it easier for residents to be more efficient by knowing how satisfied and comfortable residents are. This system was created using the PIECES Framework with measurements from 6 aspects, namely from the aspects of Performance, Information, Economics, Control, Efficiency, Service from the results of the Pieces Analysis showing that the measurement of the level of satisfaction of system users. This system is intended for residents who want to make monthly contribution payments, find out about the activities being carried out, provide criticism and suggestions, find out announcements, request letters if needed to analyze user satisfaction with deductions which results in an acquisition score of 3,610 which is the average and gets the final score which is satisfying. So it was concluded that users, namely citizens, can use the application that has been designed.